1992
DOI: 10.1177/00220345920710010101
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Degradation and Reduced Fracture Toughness in Aged Composites

Abstract: Qartz- and barium-glass-filled composites aged for more than one year in ethanol experienced a significant reduction in fracture toughness (K1c), essentially identical to that experienced after two months of aging. This reduction is mainly attributed to a softening of the resin matrix, but cracking within the resin and at the filler/matrix interface, as revealed by SEM microscopy, may also have contributed. No significant cracking could be seen in the composites aged in water. Composites post-cured at temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
1
12

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 26 publications
4
104
1
12
Order By: Relevance
“…Organic solvents, as Ethanol and MEK, showed more detrimental effect on the mechanical properties compared to water storage. Several studies have demonstrated more complete extraction of monomers and oligomers with the organic solvents that could explain their stronger impact on the mechanical properties [8,12,45,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic solvents, as Ethanol and MEK, showed more detrimental effect on the mechanical properties compared to water storage. Several studies have demonstrated more complete extraction of monomers and oligomers with the organic solvents that could explain their stronger impact on the mechanical properties [8,12,45,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…From a material aspect, the performance of the resincomposite restoration depends on several factors including the monomer system, the filler type, filler loading and the extent of cure [7]. Degradation of resin-composite restorations in the oral environment can be simulated by the use of different food simulating solvents which are known to cause different effects on the mechanical properties of the restoration and its longevity [4,[8][9][10]. Similar polarity of a particular solvent and a substance will tend to make them mutually soluble, different polarity on the other hand will make the solubility difficult [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the opposite was found for resin-based cements. This might be due to the enhanced ability of ethanol to penetrate and swell the crosslinked polymer network in comparison to water 29) . The uptake of water or solvent by a resin-based matrix may cause swelling, and a reduction of interchain interactions that may soften the resin 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Many mouthrinses include ethanol in their composition, and ethanol may accelerate the hydrolytic degradation of resin-based materials 28) . On this ground, subsurface and surface degradation of resin composites can be reproduced in the laboratory by storage in 50:50 ethanol:water solution 29,30) , which is listed as a food-simulating liquid in the U.S. Food and Drug Administration (FDA) Guidelines. The purpose of this study was to measure the solubility, sorption, and dimensional change of eight luting cements (six resin-based and two resinmodified glass ionomer cements) in two different solutions: 50% ethanol:water and distilled water.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of composite resins in the oral environment is considered to be attributed to the resin matrix, filler particles, and hydrolytic instability of silane coupling agent at the polymer-silica interface [28][29][30][31][32][33][34][35] . After one-year water storage in the present study, all composites showed higher flexural strengths in comparison with their immediate values.…”
Section: Discussionmentioning
confidence: 99%